2015
DOI: 10.3389/fnbeh.2015.00171
|View full text |Cite
|
Sign up to set email alerts
|

A cross-species genetic analysis identifies candidate genes for mouse anxiety and human bipolar disorder

Abstract: Bipolar disorder (BD) is a significant neuropsychiatric disorder with a lifetime prevalence of ~1%. To identify genetic variants underlying BD genome-wide association studies (GWAS) have been carried out. While many variants of small effect associated with BD have been identified few have yet been confirmed, partly because of the low power of GWAS due to multiple comparisons being made. Complementary mapping studies using murine models have identified genetic variants for behavioral traits linked to BD, often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 128 publications
(172 reference statements)
0
23
0
Order By: Relevance
“…In addition, strict p-value threshold with high multiple testing corrections was also believed to lose many positive loci [35,36]. Joint analysis of human GWAS and mouse genetics would help to "rescue" some of the 'missing' heritability [5,34,[37][38][39]. In the present study, we identified 48 genes in the trait-associated modules which have been reported in human GWAS with p < 10 -4 .…”
Section: Discussionmentioning
confidence: 64%
“…In addition, strict p-value threshold with high multiple testing corrections was also believed to lose many positive loci [35,36]. Joint analysis of human GWAS and mouse genetics would help to "rescue" some of the 'missing' heritability [5,34,[37][38][39]. In the present study, we identified 48 genes in the trait-associated modules which have been reported in human GWAS with p < 10 -4 .…”
Section: Discussionmentioning
confidence: 64%
“…Some previous studies have linked GWAS results to evidence from mice. [43][44][45] By systematically linking well-powered GWAS summary results with corresponding phenotypes in thousands of mice and using additional databases to evaluate their expression during murine renal development, our approach is very comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible to map Mendelian traits and even quantitative traits with modest LOD scores with good precision, even when using a small numbers of strains [75][76][77] . Second, a good way to transition from QTLs to specific genes, variants, and mechanisms is often to use complementary resources such as panels of common inbred strains, Collaborative Cross (CC), or Diversity Outbred (DO) cases, efficient screens of candidate genes using in vitro and in vivo assays 48,76 , and even human genome-wide association study (GWAS) data [78][79][80][81][82] . But the most obvious way to improve precision and power is to simply use a larger numbers of strains.…”
Section: Improved Mapping Of Bxd Phenome and Omics Datamentioning
confidence: 99%